2016
DOI: 10.1038/srep39302
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation drives chondrogenesis of mesenchymal stem cells in the absence of exogenous growth factors

Abstract: Electrical stimulation (ES) is known to guide the development and regeneration of many tissues. However, although preclinical and clinical studies have demonstrated superior effects of ES on cartilage repair, the effects of ES on chondrogenesis remain elusive. Since mesenchyme stem cells (MSCs) have high therapeutic potential for cartilage regeneration, we investigated the actions of ES during chondrogenesis of MSCs. Herein, we demonstrate for the first time that ES enhances expression levels of chondrogenic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 77 publications
7
84
0
Order By: Relevance
“…Note that, the proliferation rate is higher when the applied voltage is higher. Their findings agree with what prior works have suggested that electrical stimulation may induce cell proliferation or even differentiation 27, 28, 29. The proposed multifunctional pipette could have a potential use as a highly localized single cell electrical stimulator for biological studies and other applications, in addition to examples demonstrated in the current work.…”
Section: Resultssupporting
confidence: 92%
“…Note that, the proliferation rate is higher when the applied voltage is higher. Their findings agree with what prior works have suggested that electrical stimulation may induce cell proliferation or even differentiation 27, 28, 29. The proposed multifunctional pipette could have a potential use as a highly localized single cell electrical stimulator for biological studies and other applications, in addition to examples demonstrated in the current work.…”
Section: Resultssupporting
confidence: 92%
“…For example, timely application of TGF-β3 and BMP-2 in sequence is crucial for successful MSC chondrogenesis [19,20]. In addition, mechanical, electrical, or other material/ structural stimulations can initiate MSC chondrogenesis without the key stimuli such as TGF-βs or other molecules [21–23]. Real-time feedback with the miR-145-5p responsive reporter could help enhance timing of these events/stimuli to potentially facilitate these mechano-dynamic TE cartilage optimizations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a pulse-number-dependent downregulation of mitochondrial function and cell numbers was observed by Hall et al (2007) for nsPEFs. 3 d of PES would not cause significant cell death, while 7 d of PES would cause significant cell death (Kwon et al, 2016). The formation of pores caused by PES increases due to the increase in pulse number (Yogesh, 2016).…”
Section: Names Of Devicesmentioning
confidence: 99%
“…PES has the unique ability to induce reversible pore formation in plasma membranes within seconds, (Pakhomov et al, 2015). Pores that form on plasma membranes are temporary and reversible when an electric field strength of about 0.1-20 kV/cm and pulse durations of 10 ns-10 ms are applied (Kirawanich et al, 2010;Kotnik et al, 2015). These temporary pores have been widely used in biomedical applications, including delivery of biomolecules, such as DNA, RNA, and proteins -commonly referred to as electroporation or electrofusion (Cemazar et al, 2013;Schoellhammer et al, 2014) -as well as drugs (Okino and Mohri, 1987).…”
Section: Vsdsmentioning
confidence: 99%